Pembinaan Keagamaan dalam Meningkatkan Penerimaan Diri Penerima Manfaat Rumah Singgah Shelter Sehati Dompet Dhuafa di Jakarta Pusat - Puji Rahayu, Retno Puji; Arwan, Artiarini Puspita (Jurnal Penyuluhan Agama, 2025)
Abstract: Shelter Sehati Dompet Dhuafa provides temporary housing for patients and their families undergoing treatment. In this challenging situation, self-acceptance is an important aspect for an individual's psychological well-being. Religious guidance carried out at the shelter aims to provide moral and spiritual support, which is expected to increase the self-acceptance of beneficiaries. This study aims to explore religious guidance activities in increasing the self-acceptance of beneficiaries at Rumah Singgah Shelter Sehati Dompet Dhuafa in Central Jakarta. Guidance activities carried out iclude congregational prayer, fiqh studies, and regular religious studies. The research method used is qualitative with a phenomenological approach, which involves in-depth interviews with beneficiaries and observations of guidance activities. The results of the study indicate that religious guidance can increase the self-acceptance of beneficiaries. Before joining the program, many beneficiaries had difficulty accepting their psychological conditions due to the treatment process such as anxiety, depression and trauma. However, after being involved in guidance activities, there was a clear increase in self-acceptance, which was marked by their ability to come to terms with difficult circumstances and reduce feelings of anxiety and depression.Abstrak: Shelter Sehati Dompet Dhuafa menyediakan hunian sementara bagi pasien dan keluarga yang sedang menjalani perawatan. Dalam situasi yang penuh tantangan ini, penerimaan diri merupakan aspek penting bagi kesejahteraan psikologis individu. Pembinaan agama yang dilaksanakan di shelter bertujuan untuk memberikan dukungan moral dan spiritual yang diharapkan dapat meningkatkan penerimaan diri penerima manfaat. Penelitian ini bertujuan untuk mengeksplorasi kegiatan bimbingan agama dalam meningkatkan penerimaan diri penerima manfaat di Shelter Rumah Singgah Sehati Dompet Dhuafa Jakarta Pusat. Kegiatan bimbingan yang dilaksanakan meliputi shalat berjamaah, kajian fiqih, dan kajian agama rutin. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan fenomenologi yaitu wawancara mendalam kepada penerima manfaat dan observasi kegiatan bimbingan. Hasil penelitian menunjukkan bahwa bimbingan agama dapat meningkatkan penerimaan diri penerima manfaat. Sebelum mengikuti program, banyak penerima manfaat yang mengalami kesulitan menerima kondisi psikologisnya akibat proses perawatan seperti kecemasan, depresi dan trauma. Namun, setelah terlibat dalam kegiatan bimbingan, terjadi peningkatan penerimaan diri yang nyata, yang ditandai dengan kemampuan mereka untuk menerima keadaan sulit dan mengurangi perasaan cemas dan depresi.